The lymphocele conundrum: incidence and management in early renal transplants - Abdul Ahad, Usman; Mahar, Naveed Ahmed; Hassan Qureshi, Harris; Kalwar, Sara (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the incidence of post-transplant lymphocele, identify risk factors, and analyse the effectiveness and outcomes of different management approaches. Method: The prospective, descriptive study was conducted at the Department of Renal Transplant, Sindh Institute of Urology and Transplantation, Karachi, from February 25, 2021, to December 25, 2022, and comprised transplant patients. Ultrasound was performed in all patients presenting with symptomatology attributed to lymphocele. Any peri-graft collection was labelled as lymphocele if creatinine level of aspirated fluid was similar to that of serum creatinine level of the patients. Data was analysed using SPSS 23. Results: Of the 300 patients, 230(76.7%) were males and 70(23.3%) were females. The overall mean age was 37.33±8.70 year. There were 18(6%) patients with diabetes, 248(82.7%) with hypertension and 38(12.7%) were obese. The frequency distribution of lymphocele was observed in 22(7.3%) patients, and the mean diameter of lymphocele was 12.50±1.68 cm. Conclusion: Lymphatic complications, particularly lymphocele, continue to pose a surgical challenge in kidney transplant recipients, primarily resulting from the extensive dissection of the lymphatics during the transplantation procedure. Key Words: Lymphocele, Renal transplantation, Chronic kidney disease.